2017
DOI: 10.1038/onc.2017.55
|View full text |Cite
|
Sign up to set email alerts
|

Sox2 is dispensable for primary melanoma and metastasis formation

Abstract: Tumor initiation and metastasis formation in many cancers have been associated with emergence of a gene expression program normally active in embryonic or organ-specific stem cells. In particular, the stem cell transcription factor Sox2 is not only expressed in a variety of tumors, but is also required for their formation. Melanoma, the most aggressive skin tumor, derives from melanocytes that during development originate from neural crest stem cells. While neural crest stem cells do not express Sox2, expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 45 publications
(54 reference statements)
1
36
0
Order By: Relevance
“…Similarly as previously shown [73], vemurafenib resistance was developed independently from SOX2 expression in drug-naïve cells, however, while in the study of Cesarini et al, SOX2 was strongly upregulated only in one out of three vemurafenib-resistant cell lines, in our study SOX2 upregulation was observed in all six PLXR cell lines. As several reports suggest genetic context-dependent role of SOX2 in melanoma [73][74][75][76][77], regulation of SOX2 expression and the role of this transcription factor in resistant melanoma cells remain to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly as previously shown [73], vemurafenib resistance was developed independently from SOX2 expression in drug-naïve cells, however, while in the study of Cesarini et al, SOX2 was strongly upregulated only in one out of three vemurafenib-resistant cell lines, in our study SOX2 upregulation was observed in all six PLXR cell lines. As several reports suggest genetic context-dependent role of SOX2 in melanoma [73][74][75][76][77], regulation of SOX2 expression and the role of this transcription factor in resistant melanoma cells remain to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…If SOX2 is dispensable following metastasis in mHNcSCC as in metastatic malignant melanoma (58), a correlation between low SOX2 expression levels and a more aggressive cancer may be expected. However, Li et al (59) demonstrate that SOX2 is a downstream target of the Hippo effector TAZ in HNcSCC, which is capable of reprogramming differentiated cancer cells into CSCs, and that SOX2 and TAZ upregulation are both associated with poorer overall survival in HNcSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Sox2 is also overexpressed in a variety of tumors (Barone, 2018;Cesarini et al, 2017;Schaefer et al, 2017). The discovery of cancer stem cells (CSC), a subset of tumor cells able to behave as "tumor-reinitiating cells", capable to reform the tumor of origin following conventional chemotherapy (to which CSC are usually resistant) (Nicolis, 2007;Singh et al, 2004), led to the hypothesis that Sox2 may retain, in these pathological stem cells, an essential role (Barone, 2018;Nicolis, 2007;Wuebben & Rizzino, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the importance of SOX2 in tumorigenesis and CSC was widened to various different tumor types: for example, SOX2 amplification was identified as an oncogenic driver of esophageal and lung squamous cell carcinoma, a common type of lung cancer (Bass et al, 2009), and SOX2 was found to be required within skin tumors stem cells (Boumahdi et al, 2014). An exception to these findings is represented by the Sox2-expressing neural crest-derived tumor melanoma; indeed, Sox2 conditional deletion in two different mouse models showed that Sox2 is entirely dispensable for tumorigenesis in both cases (Barone, 2018;Cesarini et al, 2017;Schaefer et al, 2017). Overall, these findings extend the significance of the study of the "dark side of Sox2" (Wuebben & Rizzino, 2017), i.e.…”
Section: Introductionmentioning
confidence: 99%